Uji Determinan Motivasi Wanita Berwirusaha: Studi Empiris Pada Mahasiswi Di Kabupaten Klaten - Arif Julianto Sri Nugroho; Sukasih Ratna Widayanti; Dandang Setyawanti; Endang Eko DS; Abdul Haris; Agung Nugroho Jati; Tasari Tasari (Praxis : Jurnal Sains, Teknologi, Masyarakat dan Jejaring, 2021)
This study aims to test the model whether attitude towards, subjective norms, perceived behavior control in the theory of Planned Behavior have a positive influence on entrepreneurial intentions and behaviors of private university female students in Klaten Regency. The research design was carried out using a quantitative method which explains the causal relationship between one dependent variable which is influenced by three independent variables and one mediating variable. Hypothesis testing is formulated in the model using the multivariate test. The population in the research were all university students in the Klaten Regency area who had started the initial ultra-micro business. The sampling technique was carried out by purposive sampling as many as 180 respondents of female students as initial business actors.The final result of the quantitative model test using Structural Equation Modeling (SEM) shows that there is a positive influence on attitude towards entrepreneurship and perceived behavior control on entrepreneurial intentions and behaviors. Meanwhile, one variable in the form of subjective norms does not significantly influence it. Future research can expand the model through testing the antecedents of intention to behavior by developing research designs through experimental research.